UPAYA MENINGKATKAN KEMAMPUAN BERHITUNG MENGGUNAKAN JARITMATIKA SISWA KELAS 2 SDN GALENGDOWO 2 WONOSALAM - Adib Jion Satriyo (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
This research was conducted to overcome the problem of low numeracy skills in grade 2 students of SD Negeri Galengdowo 2 Wonosalam. Therefore the researchers made efforts to improve students' reading skills through the Jaritmatika method. This research involved 40 grade 2 students of SD Negeri Galengdowo 2 Wonosalam. The design of this study was classroom action research. From the results of the research, the average score in cycle I was 62.41% of 40 grade 1 students at SD Negeri Galengdowo 2 Wonosalam. Whereas in cycle II the learning completeness that has been achieved classically is 74.88%.